(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
The term ‘closed community’ is used to refer to a population of people living together continuously with limited contact with others outside that specific community. They share social amenities such as toilets, recreation facilities, wash rooms, water supply and at times sleeping places. They are in close contact with minimum interruption for long periods. Typical examples include military camps, ship crew on extended period at sea, refugee camps, mental hospitals and prisons. Boarding schools are examples of semi-closed communities. Similarly, some patients in hospital wards could be viewed as semi-closed communities. The term ‘closed community’ must not be confused with ‘gated community’ which refer to residential community containing strictly controlled entrance with a closed perimeter wall but otherwise live independent of each other with no shared social facilities